Memahami Keputusan Pembelian Produk Sunscreen Azarine: Peran Pemasaran Influencer dan Citra Merek pada Mahasiswa Kota Medan - Sihotang, Anindya Windy; Greasia Oriza Sitio; Putri Patricia Sitinjak; Onan Marakali Siregar; Yossie Rossanty (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this research is to learn how certain students in Medan City are influenced to buy Azarine sunscreen products by influencer marketing and brand image. More and more people, particularly students, are realizing the need of preventing sun damage to their skin, therefore sunscreen solutions have quickly become an integral part of skin care regimens. Researchers in this research used a quantitative approach by surveying people who had used Azarine products. Using SPSS software version 29, the data that was obtained was examined. The findings show that consumers are influenced by both favorable brand image and influencer marketing, which has a major impact on their purchase choices. There is a significant relationship between the dependent variable and each of the independent variables.